What can governments do to boost FDI for sustainable development? - Martin Wermelinger (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
FDI can support sustainable development, but benefits are not automatic. This Perspective explores public policy considerations to increase the positive impacts of FDI - ranging from policy coherence, regulatory balance and smart use of tax incentives to the role of investment promotion agencies and the donor community as facilitators.
Keywords: 330